2016
DOI: 10.1111/ene.12960
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid chitinase‐3‐like 2 and chitotriosidase are potential prognostic biomarkers in early multiple sclerosis

Abstract: CHI3L2 and chitotriosidase are promising biomarkers in patients with a first demyelinating episode. Our findings thus support a role for these proteins as biomarkers in early MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 31 publications
2
41
0
1
Order By: Relevance
“…24 Elevations in CHIT1 have also been observed in lysosomal storage diseases 25 and multiple sclerosis, 26 whereas increased CSF CHI3L1 level is associated with progression to multiple sclerosis following a clinically isolated syndrome. 24 Elevations in CHIT1 have also been observed in lysosomal storage diseases 25 and multiple sclerosis, 26 whereas increased CSF CHI3L1 level is associated with progression to multiple sclerosis following a clinically isolated syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…24 Elevations in CHIT1 have also been observed in lysosomal storage diseases 25 and multiple sclerosis, 26 whereas increased CSF CHI3L1 level is associated with progression to multiple sclerosis following a clinically isolated syndrome. 24 Elevations in CHIT1 have also been observed in lysosomal storage diseases 25 and multiple sclerosis, 26 whereas increased CSF CHI3L1 level is associated with progression to multiple sclerosis following a clinically isolated syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Chitinases predict prognosis in early MS. The most recent evidence indicates that CHI3L2 performs better than CHI3L1 and predicts the development of MS after the first demyelinating episode, 98 although in the earlier work, CHI3L1 was mostly studied and a similar predictive capability was demonstrated. 99 Consistency of findings.…”
Section: Neurofilamentsmentioning
confidence: 99%
“…In the human brain, ChT is proposed to be synthesized by microglia and high CSF ChT levels have been shown in several neurological conditions [14][15][16]. Previous reports revealed that ChT is increased in CSF in patients with ALS and proposed this enzyme as a potential biomarker for ALS [17][18][19].…”
Section: Introductionmentioning
confidence: 99%